Fabrication and experimental characterization of eccentrically layered scatterers in 2-D Phononic materials - Samarakoon, S. M. Disna Priyadarsani (Kansas State University, 2010)
The study on artificially created materials has much evidence of naval properties. Phononic Crystals (PCs) are new class of artificially constructed materials. They have a large number of scattering inclusions that are embedded in a homogeneous host material. These scatterers are arranged in periodic lattice structures. The scatterers and host materials are usually either solids or fluids. Phononic materials are useful due to their ability to hinder the existence of certain frequencies over which the propagation of elastic and acoustic waves are forbidden. The formation of phononic band gaps (PBGs) in PCs is determined by the material properties and the geometry of the periodic lattice structures. Some PCs have full band gaps [14, 55] while others have partial band gaps [35]. Although the study of PCs is an attractive area for many researchers, the investigations on PCs are just emerging. The aim of the thesis is to study on perform fabrication and experimental characterization of 2-D PCs having eccentrically layered scatterers. In addition, the influence of the eccentricity of the layered scatterers on the amplitude spectrums are experimentally observed. Hence, the main objective in this work is to characterize the influence of the eccentricity orientation angles on the transmitted amplitude spectra. The layered scatterers were created by inserting the paraffin-coated stainless steel rods into the cavities. Two sets of stainless steel rod diameters (2 mm and 2.5 mm) were used. The eccentricity orientation angles of scatterers were changed from 0 degree to 90 degrees at the increment of 22.5 degrees. Ultrasonic waves were introduced into the test pieces to observe the propagated waves through the material. The ultrasonic Through Transmission Test (TTT) followed by signal processing techniques was employed to produce the transmitted spectra of PCs. The frequency dependent amplitude spectrums were observed at the chosen frequency ranges with the help of MATLAB and Fast Fourier Transformation (FFT) function. The results show that the geometry and the material parameters change the attenuation of amplitudes by hindering the wave propagation. This leads PC as a good candidate for a sound barrier for controlling the wave propagation or vibrations within the chosen frequency ranges. Keywords: Phononic Crystal/s (PC or PCs); Phononic Band Gap/s (PBG or PBGs); Through Transmission Test (TTT), Fast Fourier Transformation (FFT), Square array, Triangular array, Amplitude spectrum/ Spectra, Eccentrically layered scatterers
Keywords: Phononic; Engineering, Mechanical (0548)